An Equivalent Hybrid Model for a Large-Scale Modular Multilevel Converter and Control Simulations - Mohammed Alharbi; Semih Isik; Subhashish Bhattacharya (IEEE Access, 2022)
Modular multilevel converter (MMC) is adopted mainly for high voltage applications with many power blocks per arm. Before commissioning a large-scale MMC application, it is vital to simulate and study internal and system-level dynamics. However, it is challenging to simulate an MMC with many SMs in EMT simulation tools due to simulation time and computation burden. Therefore, several simplified modeling techniques are proposed to reduce the challenges. Even though the existing models reasonably reduce the computation complexity and simulation time, there are still challenges as the internal dynamics of an MMC cannot be fully captured. On the other hand, the detailed equivalent models capture the internal dynamics, but the simulation complexity and the time increase. Therefore, it is still a need for better, faster, and more accurate simulation models to study the system-level and internal dynamics of an MMC. Therefore, this paper proposes a hybrid simulation model for a large-scale MMC application using a scale-up control structure method. The proposed method is verified in the MATLAB/Simulink simulation tool. Besides, the proposed model is tested and verified at the Real-Time Digital Simulator (RTDS) in a Hardware-in-Loop (HIL) environment.